Research on the Optimum Content of Basalt Fiber to Improve the Performance of Core Wall Asphalt Concrete - YANG Manzhi (Renmin Zhujiang)
In order to find out the optimum content of basalt fiber to improve the performance of core wall asphalt concrete,this paper studies the physical and mechanical properties of the core wall asphalt concrete made up of 0%~0.8% (that is the mass ratio to asphalt concrete) basalt fiber by uniaxial compression test,bending test,tensile test and water stability test of the core wall asphalt concrete.The results show that the physical and mechanical properties of the core wall asphalt concrete with basalt fiber are improved,which reach the best as follows when the content of basalt fiber is 0.6%,50.39% increasing in the compressive strength,44.22% in the bending strength,154.72% in the tensile strength obviously,and 25.61% in the water stability coefficient.The results show that the physical and mechanical properties of the core wall asphalt concrete can be effectively improved after adding basalt fiber,especially with the optimum content of 0.6%.